Fetal Hydronephrosis in the Second and Third Trimester of Pregnancy and Six Months Follow-up after Birth - Zahra Akbarian-rad; Zahra Shafizadeh; Fatemeh Nasiri-Amiri; Sahar Sadr Moharerpour; Hossein Ali Nikbakht; Zeinab Pahlavan; Fatemeh Shafizadeh; Mohsen Haghshenas mojaveri; Mohammadreza Tabatabaie (Iranian Journal of Neonatology, 2025)
Background: Prenatal hydronephrosis (PNH) may be associated with congenital abnormalities in the urinary tract. This study aimed to determine and follow up on the fetus diagnosed with PNH until the first six months after birth.Methods: This prospective longitudinal study was conducted from May 2021 to July 2022 in fetuses who were diagnosed with PNH based on the size of the anterior-posterior diameter of the renal pelvis (APRPD) by a perinatologist with an S W 80 ultrasound machine. If it is ≥ 4 mm in the 2nd and ≥ 7 mm in the 3rd trimesters, it is considered PNH. These infants were followed up until the first six months after birth. Data analysis was performed using SPSS 20, Chi-square, Fisher's exact, and T-tests.Results: Of the 56 eligible fetuses, 50 fetuses were followed up. The mean gestational age at the time of diagnosis of PNH was 20.48 ± 5.37 weeks. Twenty cases of PNH (45.45%) spontaneously improved until birth. Thirty cases had hydronephrosis in the first week after birth, 16 of which (53.33%) were bilateral. The cause of PNH in 90% is idiopathic. Other causes include polycystic kidney, vesicoureteral reflux, and posterior urethral valve. One case died in the first week after birth. Forty-three cases had spontaneous recovery of PNH by six months, and 6 cases (12%) had adverse outcomes. The severity of PNH in the 3rd trimester had a significant relationship with adverse outcomes (P=0.001). The APRPD in the 3rd trimester has more sensitivity and specificity than in the 2nd trimester for predicting adverse outcomes after birth.Conclusion: In most cases, the cause of PNH is idiopathic, and the resolution of PNH occurs up to 6 months after birth. Moderate and severe PNH was associated with a poorer outcome and requires more follow-up and intervention.